Maternal high-dose folic acid during pregnancy and risk of asthma in children: an evidence based review - Ramôa, Andreia (2018)
Objective: Maternal supplementation with folic acid has a positive effect on the prevention of neural tube defects. The relationship between high-dose supplementation of folic acid (5mg) and the development of asthma in children is controversial. The aim of this review is to appraise the evidence on the association between the supplementation with high doses of folic acid during pregnancy and the risk of developing asthma in childhood. Data sources: National Guideline Clearinghouse, Canadian Medical Association Practice Guidelines, Cochrane Library, DARE, Bandolier, PubMed and Index of Portuguese Medical Journals. Review method: We searched meta-analyses, systematic reviews, original studies and clinical guidelines published between July/2006 and July/2016 in Portuguese, English, Spanish and French languages, using the MeSH terms: ‘Folic Acid’, ‘Asthma’ and ‘Pregnancy’. The Strength of Recommendation Taxonomy (SORT) scale of the American of Family Physicians was used to assign evidence levels and strength of recommendation grades. Results: Five studies were selected from a total of 29 articles found, including two meta-analyses and three original studies. Results from meta-analyses do not support an association between periconceptional folic acid supplementation and increased risk of developing childhood asthma. However, none of the studies included in the meta-analyses stratified the results according to the dose of folic acid used during pregnancy and risk of asthma. On the other hand, original studies suggest that supplementation with high doses of folic acid during pregnancy may increase the risk of developing asthma in childhood. Conclusions: Evidence on the association between folic acid supplementation during pregnancy and the risk of developing asthma during childhood is controversial. Studies showing results stratified according to the dose of folic acid reveal that high doses (>800mg) are associated with an increased risk of developing childhood asthma (SORT B).